FRI0002 Analysis of b cells and t cells subpopulations and collagen specific t cell repertoire in juvenile idiopathic arthritis patients. (12th June 2018) - Di Sante, G.; Caparello, M.C.; Tolusso, B.; Di Mario, C.; Valentini, M.; Ria, F.; Ferraccioli, G.; Cimaz, R.; Gremese, E.
Abstract : Background: The cause of the breach in immune tolerance in the arthritic joint is not fully understood; many associations between subsets of JIA and HLA and non-HLA molecules have been described. 1 An important role is played by T cell population, that is driven also by its specific T cell receptor (TCR) repertoire; it has been previously observed that synovial T cells exhibit oligoclonal TCR repertoires. 2 Objectives: To examine frequency and distribution of human Collagen261–273 -specific T cells and the phenotypes of B and T cells subpopulations and the role of DR alleles in JIA, in order to find new biomarker for management of JIA. Methods: HLA genotyping and CDR3 TRBV-TRBJ spectratyping (TCR repertoire Immunoscope analysis) 3 were performed on Peripheral blood mononuclear cells (PBMCs) on a total of 40 Juvenile Idiopathic arthritis (JIA) patients (and in 2 cases also in samples of Synovial fluids) and 6 Healthy Controls. The enrolled patients were mainly affected by polyarticular arthritis (26 out 40) and were free of CS (38 out 40) and cDMARDS (24 out 40) treatments. The mean disease duration was 37 months. All the patients were ACPA and RF negative and the mean ESR and PCR values were respectively 39.5±32.4 mm/h and 17.5±37.4 mg/L. B cells and T cells subpopulations were analysed by flow cytometer assays. Results: In our cohort 4 patients were DR4+ (10%) and 8 were DR1+ (20%). In the entire cohort no differences were found in terms of B cells subpopulations, but dividing the cohort on the basis of the age of disease onset it was possible to identify a upregulation of Switched B cells compartment in younger patients more than the JIA with an exordium after 12 years, confirming the data recently published. 4 We checked for the presence of collagen specific TRBV25-TRBJ2.2 T cells, whom the expansion were significantly associated with disease activity and modulated by therapy in RA patients, as described in our previous work. 3 Our preliminary results in a so small cohort of patients indicate that the same expansion in JIA patients seems to associate with JADAS and DR4/DR1 positivity, independently from any conventional and biological treatment. Moreover our T cells subpopulation analysis allowed to find interesting correlation between Tregs and switched memory, Tregs and double negative (IgD neg /CD27 neg ) B cells (r=0.476, p=0.04) and Tregs and DR4/1 positivity (0.432 p=0, 03) and between CD27 high /CD38 high cells and Il17a producing cells (r=0.414, p=0.04); these correlations are more significant in JIA patients with a disease onset at a young age (age <6 years). Conclusions: These preliminary results suggest that the analysis of collagen specific T cells repertoire, T and B cells subpopulations and HLA-DR haplotype can provide useful information to characterise peculiar details of each JIA patient References: [1] Ravelli, Martini. Lancet2007. [2] Wedderburn LR, et al. Int immunol1999. [3] Di Sante, et al. Ebiomedicine 2015. [4] Marasco E, et al. Arth Rheum 2018. Disclosure of Interest: None declared